2010
DOI: 10.1038/emboj.2010.272
|View full text |Cite
|
Sign up to set email alerts
|

The structure of an Iws1/Spt6 complex reveals an interaction domain conserved in TFIIS, Elongin A and Med26

Abstract: Binding of elongation factor Spt6 to Iws1 provides an effective means for coupling eukaryotic mRNA synthesis, chromatin remodelling and mRNA export. We show that an N-terminal region of Spt6 (Spt6N) is responsible for interaction with Iws1. The crystallographic structures of Encephalitozoon cuniculi Iws1 and the Iws1/Spt6N complex reveal two conserved binding subdomains in Iws1. The first subdomain (one HEAT repeat; HEAT subdomain) is a putative phosphoprotein-binding site most likely involved in an Spt6-indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…The ARM domain shared by elongation factor TFIIS and Med26 enables yeast TFIIS to interact with SAGA and Med13 (Diebold et al, 2010). Secondary structure analysis showed a similar pattern of conservation between the Arabidopsis and human Med26 ARM domains (Fig.…”
Section: Structural Conservation Of Mediator Submodules In Plantsmentioning
confidence: 63%
“…The ARM domain shared by elongation factor TFIIS and Med26 enables yeast TFIIS to interact with SAGA and Med13 (Diebold et al, 2010). Secondary structure analysis showed a similar pattern of conservation between the Arabidopsis and human Med26 ARM domains (Fig.…”
Section: Structural Conservation Of Mediator Submodules In Plantsmentioning
confidence: 63%
“…This interaction, believed to be dynamic and to govern the ability of Spt6 to interact with nucleosomes (McDonald et al 2010), is required for several steps in transcription-from initiation (Zhang et al 2008) to histone modifications, RNA processing, and mRNA export (Yoh et al 2007(Yoh et al , 2008. Structural analyses of Spn1 and the Spn1-Spt6 complex have recently been described (Diebold et al 2010a;McDonald et al 2010;Pujari et al 2010). Although these two proteins appear to interact, they do not have the same pattern of association across the yeast genome .…”
Section: Spt6 and Fact: Factors Controlling Transcriptional Integritymentioning
confidence: 99%
“…Domain I, the first 130 amino acids, was not visible in the structure, and biochemical and genetic studies indicate that it is dispensable for promoting transcript cleavage and rescuing backtracked RNAPII (9,46). While dispensable for the biochemical activity of TFIIS, domain I interacts with several transcription factors (12,(47)(48)(49). In particular, a recent study showed that the N terminus is required for TFIIS recruitment into the preinitiation complex (50).…”
Section: Ccr4-not Interacts With Tfiis and Enhances Its Recruitment Imentioning
confidence: 99%